Exploring U.S. students' takeaways from a cross-Pacific COIL project - Xuan Jiang (University of Groningen Press, 2022)
English imperialism has helped form the dominance of one-way communication from Native English Speakers (NESs) to English learners, resembled in the existing literature of international education and exchange education (i.e. study abroad programs). Such unbalanced foci in the ongoing scholarship of exchange programs, including Virtual Exchange (VE), do not equally represent the whole participating parties of collaboration and furthermore overlook the learning needs and achievements from NESs. Noticing such a gap in the scholarship, the author intended to explore what NESs and native speakers of more than English have taken away from a Collaborative Online International Learning (COIL) project between a university in China and a Hispanic-Serving Institution in the U.S. Twenty-one U.S. students in a writing-as-processes course were asynchronously collaborated with 20 students in a reading-writing course in China over ten weeks. The COIL data of this case study was from U.S. students' reflections on the peer review giving and given and their COIL reflections. The qualitative findings revealed that Peer Feedback (PF) via COIL broadened participants' insight about contrastive rhetoric, English as pluralistic, and cross-cultural communication. The COIL project also offered multi-dimensional enrichment and promoted 21st century skills in general. The participants expected some form of continuous VE projects, similar to the current COIL project, in the subsequent semesters. Those findings implied practical considerations of how to further develop COIL - synchronous or/and asynchronous modes, multi-layered collaborations, individual and collective communication, and a balance among students' autonomy, technology support, and instructors' affordability of additional arrangements for details. The significance of the study lies in the fact that the findings would help mitigate and balance scholarly attention to students' takeaways from both participating parties.